Prophylactic laparoscopic adnexal surgery with low-pressure CO2 insufflation for ovarian cysts during the late first trimester or second trimester of pregnancy - K. Chikazawa; K. Imai; T. Kuwata; K. Takagi (IMR Press, 2020)
The current guidelines for endoscopic management do not contraindicate laparoscopic surgery in pregnant women; a few studies have reported on this, particularly in Japan. We aimed to evaluate the feasibility of prophylactic laparoscopic adnexal surgery during the late first trimester and second trimester for the prevention of adnexal torsion. We retrospectively reviewed eight patients who underwent laparoscopic surgery for ovarian cysts during the late first trimester or second trimester (April 2012-September 2016). The general protocol of laparoscopically-assisted cystectomy was adopted, with low-pressure CO2 insufflation (8 mmHg). No complications were noted. Five women delivered; four delivered at term and one delivered preterm owing to premature membrane rupture. Pregnancy is ongoing in the remaining three women. Prophylactic laparoscopic adnexal surgery is safe and feasible for adnexal torsion prevention in women with ovarian cysts during the late first trimester or second trimester.